Efektivitas Projek Penguatan Profil Pelajar Pancasila Pada Mata Pelajaran Pendidikan Pancasila di SMK Swasta Kristen BNKP Gunungsitoli - Telaumbanua, Darisalim (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effectiveness of the project, and analyze the types of activities of the Pancasila student profile strengthening project in the Pancasila education subject at the BNKP Gunungsitoli Christian Private Vocational School. This study uses a descriptive approach, qualitative method. The research instrument is the researcher himself, with data collection techniques in the form of observation, interviews and documentation. The results of the study and discussion concluded that: First, the Effectiveness of the Pancasila Student Profile Strengthening Project in the Pancasila Education subject at the BNKP Gunungsitoli Christian Private Vocational School has been carried out effectively, starting from the design, implementation, to evaluation and reflection stages, with the theme "Voice of Democracy" with the topic "One Voice Determines the Future of the School" and the theme "Recognize My Potential" with the topic "Self-Potential Awareness". Second, the types of activities in the theme "Voice of Democracy" are making infographics about the history and types of democracy; and for the theme "Recognize My Potential", students describe and demonstrate their potential.